Allergic fungal rhinosinusitis: an overview on pathogenesis, early diagnosis and management - Suri, Neeraj; B. M., Bhavya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The objective of the study was to evaluate the criteria for diagnosing allergic fungal rhinosinusitis and to maintain permanent drainage and ventilation, while preserving the integrity of the mucosa. Methods: This is a prospective study of 50 patients with allergic fungal sinusitis with or without polyposis all of whom were treated with endoscopic debridement. Mucous sample collection, nasal secretion culture, surgical specimen handling, and histological evaluation of surgical specimens are described. All patients treated with endoscopic sinus surgery, debridement, post-operative use of steroids and antifungal therapy. Results: Fungal mucin was found in all 50 cases, histology and fungal cultures confirmed the diagnosis. Out of 50 patients, 29 were females and 21 were males, with a mean age of 32 years. The most common symptom was nasal discharge 41 (82%) cases, nasal obstruction in 38 (76%) cases, headache and facial pain in 32 (72%) cases, 7 (14%) patients had bronchial asthma. Symptoms of nasal obstruction and nasal discharge were improved in 46 (92%) cases. All preoperative versus postoperative changes in AFRS associated complaints reached statistical significance of p value <0.001 except in patients with asthma. Conclusions: Comprehensive management with endoscopic sinus surgery, oral steroids and antifungals reduces the recurrence or need for revision surgery. Long term follow up is very important.